2023
DOI: 10.1021/jacs.3c08751
|View full text |Cite
|
Sign up to set email alerts
|

K-Ion Slides in Prussian Blue Analogues

John Cattermull,
Nikolaj Roth,
Simon J. Cassidy
et al.

Abstract: We study the phenomenology of cooperative off-centering of K+ ions in potassiated Prussian blue analogues (PBAs). The principal distortion mechanism by which this off-centering occurs is termed a “K-ion slide”, and its origin is shown to lie in the interaction between local electrostatic dipoles that couple through a combination of electrostatics and elastic strain. Using synchrotron powder X-ray diffraction measurements, we determine the crystal structures of a range of low-vacancy K2M­[Fe­(CN)6] PBAs (M = N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This effect is consistent with the experimental observation of pressure-driven structural distortions in some PBAs. , The effect of temperature is formally given by the balance of entropic terms in the free energies, but one simplification is to consider the effective radii of eq to be temperature-dependent. Since one expects the thermal volume of A- and X-site ions to grow more quickly than that of the B-site, α should increase with temperature, rationalizing the thermal quenching of distortions observed experimentally. , …”
mentioning
confidence: 72%
See 1 more Smart Citation
“…This effect is consistent with the experimental observation of pressure-driven structural distortions in some PBAs. , The effect of temperature is formally given by the balance of entropic terms in the free energies, but one simplification is to consider the effective radii of eq to be temperature-dependent. Since one expects the thermal volume of A- and X-site ions to grow more quickly than that of the B-site, α should increase with temperature, rationalizing the thermal quenching of distortions observed experimentally. , …”
mentioning
confidence: 72%
“…For example, Mn­[Pt­(CN) 6 ], which with no A-site cations at all has a tolerance factor well below 1, nonetheless adopts a cubic crystal structure in which the BX 3 framework is undistorted . Instead it is by filling the A-site (i.e., increasing α) that distortions are switched on. , This behavior contrasts with that of conventional perovskites but is conceptually similar to the activation of tilts in halide hybrid perovskites through hydrogen-bonding interactions between organic A-site cations and the anionic framework . An additional complication that we will address is that PBAs are highly nonstoichiometric frameworks, and one might expect partial site occupancies to play a nontrivial role in the activation or otherwise of collective distortions.…”
mentioning
confidence: 99%
“…Further, Rietveld refinement revealed that a near identical structure and higher potassium concentration (1.871(3) per formula unit) compared to previous studies was produced (Supplementary Note 2). 5,59,60 Elemental analysis by inductively coupled plasma mass spectrometry (ICP-MS) also indicated a low-vacancy/high potassium content from the Fe:Mn ratio of 0.98 (5), giving a chemical formula of K 1.871(3) Mn[Fe(CN) 6 ] 0.98 (5) from the combined XRD/ICP-MS analysis. The material was synthesised to have as large particles as possible while maintaining performance to minimise finite-size effects and ensure D limitation in the Kang-Chueh GITT measurements.…”
Section: Potassium Manganese Hexacyanoferrate Cathodementioning
confidence: 99%